2020
DOI: 10.1177/1178638820979029
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Ketones as Therapeutic Signaling Molecules in High-Stress Occupations: Implications for Mitigating Oxidative Stress and Mitochondrial Dysfunction in Future Research

Abstract: High-stress occupations (ie, firefighters, military personnel, police officers, etc.) are often plagued by cardiometabolic diseases induced by exposure to chronic stressors. Interrupted sleep cycles, poor dietary patterns, lack of physical activity, and smoke exposure along with simultaneous psychological stressors promote chronic low-grade inflammation and excessive oxidative stress. Collectively, these data suggest that practical interventions which might mitigate the underlying pathologies of these cardiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Although ketone salts provide a practical option for fire departments as a result of lower costs, a systematic review showed that ketone salts as currently available off-the-shelf are largely ineffective at elevating bHB concentrations [,1.0 mM (19)] often resulting in a lack of any ergogenic potential. Several investigators have since speculated of a hypothesized bHB minimum threshold (;2.0 mM) to observe metabolic benefits that extend beyond performance (15,19,39,43). Therefore, the present study incorporated a KME (0.5 g/kg body mass) as opposed to a ketone salt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ketone salts provide a practical option for fire departments as a result of lower costs, a systematic review showed that ketone salts as currently available off-the-shelf are largely ineffective at elevating bHB concentrations [,1.0 mM (19)] often resulting in a lack of any ergogenic potential. Several investigators have since speculated of a hypothesized bHB minimum threshold (;2.0 mM) to observe metabolic benefits that extend beyond performance (15,19,39,43). Therefore, the present study incorporated a KME (0.5 g/kg body mass) as opposed to a ketone salt.…”
Section: Discussionmentioning
confidence: 99%
“…Each experimental trial was identical except for the drinks ingested. The present supplement dosing protocol was adopted from Evans and Egan (8) and modified based on previous pilot data aimed at achieving bHB concentrations above a theoretical minimum threshold (;2 mM) where potential metabolic effects might be observed (15,19,39,43). During each experimental trial, subjects ingested a single bolus of a given drink containing 300 ml of water in opaque bottles with either the KME (0.5 g/kg body mass) or PLA, 30 minutes before the live-burn S&R. The KME is a commercially available R-bHB (R)1,3-butanediol (KE4, Fruit Punch, KetoneAid) and was mixed with a bitter blocker (TrueBlock, Danbury, CT).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, d-3HB have been extensively explored in different fields over the past few years in relation to physical and metabolic health (Møller 2020). Interestingly, it has been proposed that d-3HB may provide protection against cardiometabolic complications in high-stress workers due to its ability to mitigate oxidative stress and inflammation (Waldman and McAllister 2020). Newman and Verdin have extensively reviewed how d-3HB was regulated and its role as an endogenous histone deacetylase (HDAC) inhibitor within the body, which was significant in modulating metabolism and diseases of aging (Newman and Verdin 2014).…”
Section: Applications Of D-3hb Across Different Fieldsmentioning
confidence: 99%
“…Various analogs of ketones continue to present unprecedented opportunities for maintenance of good health [ 17 , 25 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Optimum levels of ketones in the body have beneficial effects on brain function [ 25 , 36 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in plasma ketone levels correlate with brain ketone metabolism and provide a source of energy supply to the brain, helping to mitigate energy crises associated with neurodegenerative diseases which are characterized by a decline in the brain’s glucose metabolism [ 25 , 34 , 36 , 42 ]. Systemic presence of ketone molecules is known to promote resistance to oxidative and inflammatory stress and control transcription of genes associated with aging [ 32 , 33 , 34 , 35 , 36 , 38 , 39 , 41 , 42 ]. Although the effects of a ketogenic diet on exercise performance are controversial, administration of (R)-3-hydroxybutyl (R)-3-hydroxybutyrate ketone ester to trained cyclists has been shown to increase performance [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%